The Relationship Between Nutrional Status And Event Early Menarche In Children Aged 9-12 Years - Hartati, Lucia; Irmawati, Nurisda (Chakra Brahmanda Lentera Institute, 2024)
Background: Nutritional status in girls can affect children's sexual maturity. Overnutrition status in girls can lead to earlier menarche, this is related to the fulfillment of the nutritional needs needed by the body, especially in the reproductive organs which are well fulfilled so that the hormones estrogen and progesterone function optimally so that the menarche process can run faster than normal age. Methods: This study uses a quantitative methodology based on a cross-sectional design. Using a complete sampling technique, this research draws its sample from 63 participants. Nutrient intake is the one that stands alone. Time to first menstrual period is the dependent variable. Statistical tests were conducted using the Spearman rank test based on data collected through weighing, measuring height, and giving questionnaires to respondents. Results: With a p-value of 0.003 (p<0.05), this study demonstrated a negative connection between nutritional health and the incidence of early menarche. Conclusion: This study discovered that early menarche was linked to poor nutritional status among 9–12-year-olds in SD Negeri Karangawen 1 in Demak Regency. it is recommended that nutritional education and intervention programs be implemented for young girls, particularly those aged 9-12, in SD Negeri Karangawen 1 in Demak Regency to improve their nutritional status and address issues related to early menarche.